2017
DOI: 10.1371/journal.pmed.1002251
|View full text |Cite
|
Sign up to set email alerts
|

Association of lifelong exposure to cognitive reserve-enhancing factors with dementia risk: A community-based cohort study

Abstract: BackgroundVariation in the clinical manifestation of dementia has been associated with differences in cognitive reserve, although less is known about the cumulative effects of exposure to cognitive reserve factors over the life course. We examined the association of cognitive reserve-related factors over the lifespan with the risk of dementia in a community-based cohort of older adults.Methods and findingsInformation on early-life education, socioeconomic status, work complexity at age 20, midlife occupation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
148
1
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 151 publications
(163 citation statements)
references
References 55 publications
9
148
1
5
Order By: Relevance
“…This suggests that cognitive reserve is a formative, rather than a reflective latent indicator. 9 Building on the findings from that study, which suggested that cumulative engagement in reserve-enhancing activities might be more relevant than the specific stages at which these contributors were acquired, we devised a cognitive reserve indicator that considered simultaneous contributions of several inputs. Even though several neuroimaging and clinicopathological studies have largely supported the presence of a neural basis for efficiency and compensation, 24,25 there is still much need for methodological development of the cognitive reserve concept.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that cognitive reserve is a formative, rather than a reflective latent indicator. 9 Building on the findings from that study, which suggested that cumulative engagement in reserve-enhancing activities might be more relevant than the specific stages at which these contributors were acquired, we devised a cognitive reserve indicator that considered simultaneous contributions of several inputs. Even though several neuroimaging and clinicopathological studies have largely supported the presence of a neural basis for efficiency and compensation, 24,25 there is still much need for methodological development of the cognitive reserve concept.…”
Section: Discussionmentioning
confidence: 99%
“…27 A recent study from our group has attempted to test the relevant importance of stages (early, mid-, and late life) at which cognitive reserve exerted the largest protection against dementia risk. 9 Building on the findings from that study, which suggested that cumulative engagement in reserve-enhancing activities might be more relevant than the specific stages at which these contributors were acquired, we devised a cognitive reserve indicator that considered simultaneous contributions of several inputs. Among these, we also included social network and accumulated substantive complexity across 5 midlife occupations that were not considered in the previous study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various risk or protective factors for dementia syndrome or cognitive impairment have been suggested by numerous epidemiological studies [25]. However, we still do not know much about the mechanisms through which various lifetime experiences such as physical and mental activity, social relationships, stress experiences, personality, diet and nutrition, and sleep, and many aging-related physiological or pathological changes in the human body, such as vascular status, hormonal changes, glucose or lipid metabolism, and body mass index (BMI).…”
Section: Discussionmentioning
confidence: 99%